2016
DOI: 10.1016/j.esxm.2016.03.027
|View full text |Cite
|
Sign up to set email alerts
|

REVITALISE: A Large Observational Study Assessing the Safety and Effectiveness of Vardenafil in Men With Erectile Dysfunction and Metabolic Syndrome

Abstract: IntroductionErectile dysfunction (ED) is prevalent in men with metabolic syndrome (MetS); therefore, it is important to characterize ED treatments in this population.AimsTo investigate the safety and effectiveness of vardenafil in men with ED and MetS in a clinical setting.MethodsREVITALISE is an international, prospective, single-arm, observational study in men with ED and MetS newly prescribed vardenafil. Vardenafil was prescribed at the discretion of the treating physician in line with the marketing authori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
1
1
0
1
Order By: Relevance
“…It has been reported that androgen levels decrease as the number of MetS components increase, and low testosterone level is a predictive factor for MetS and DM (Gould et al, 2007). However, these findings were not observed in other studies (Shabsigh & Mattern, 2016;Suetomi et al, 2008). Supporting this observation, there were no significant differences in our study groups in terms of testosterone levels.…”
Section: Discussionsupporting
confidence: 68%
“…It has been reported that androgen levels decrease as the number of MetS components increase, and low testosterone level is a predictive factor for MetS and DM (Gould et al, 2007). However, these findings were not observed in other studies (Shabsigh & Mattern, 2016;Suetomi et al, 2008). Supporting this observation, there were no significant differences in our study groups in terms of testosterone levels.…”
Section: Discussionsupporting
confidence: 68%
“…For cite: Mìžnarodnij endokrinologìčnij žurnal. 2018;14 (7):645-649. doi: 10 [5]. Повна імпотенція відзначалася у 28 % чоловіків, хворих на ЦД, у той час як у загальній популяції чоловіків вона траплялася лише у 9,6 % обстежених.…”
Section: патогенетичні механізми розвитку еректильної дисфункції у чоunclassified
“…MetS, a cluster of metabolic derangements that are major risk factors for vascular disease, is one of the important threats to individuals with erectile dysfunction (ED). Phosphodiesterase type 5 inhibitor (PDE5i) therapy is currently the first-line treatment for ED, but some patient groups are either unresponsive to or contraindicated for PDE5i treatment (Shabsigh & Mattern, 2016). Hence, the aims of this study were to determine the underlying mechanisms of MetS related ED (MED) to provide novel therapeutic options.…”
Section: Introductionmentioning
confidence: 99%